Como ler poéticas digitais (perspectivas de leituras) - Vieira , Faviano Maciel (2017)
New ways of making poetry arise from new digital technologies. This new way of making poetry presents an innovative form of artistic writing, consequently poetic categories specific to the computer programs used begin to form in the systems created with these media. This demands from readers new ways of looking and interpreting, to seek an appropriate way of seeing-reading-hearing-translating the poetry. Within this new media context, the problem raised in this work is: how to read digital poetry? The aim of the thesis is to present a possible methodology for reading digital poetry, independent of the technology and computer programs available at the historical moment of its composition. Therefore, the hypothesis is that these categories will be efficient tools for such readings. Thus, in this work, conceptual issues are problematized in the context of contemporary arts; categories are formulated and presented as reading methods; and avant la lettre digital and digital poetries are analyzed in order to apply the developed method. Undoubtedly, more research is important to best situate literary criticism in the face of the poetry made with new digital technologies. This work includes theoretical dialogues within a bibliographical review of books and texts that are fundamental to the discussion of what digital poetry is and how we can read it. The theoretical basis that informs our approach is the triadic semiotics of Charles Sanders Peirce. The importance of Peircean semiotics lies in having a theoretical method that covers the study of verbal and nonverbal symbols. For Décio Pignatari (2004), Peircean semiotics is destined to play a prominent role, both in literary criticism and in theory. It is hoped, in this sense, to contribute to the general conceptual-theoretical course already existing around poetry in computational media, something which has been so well developed by authors like Julio Plaza, Antônio Risério, Philadelpho Menezes, José Augusto Mourão, Pedro Barbosa, Jorge Luiz Antonio, Alckmar Luiz dos Santos, Pedro Reis, Rui Torres, Mônica Tavares, and Amador Ribeiro Neto, just to name some important Brazilian and Portuguese researchers.